Cover Picture: Development of Small‐Molecule Cryptochrome Stabilizer Derivatives as Modulators of the Circadian Clock (ChemMedChem 9/2015). Issue 9 (13th August 2015) - Lee, Jae Wook; Hirota, Tsuyoshi; Kumar, Anupriya; Kim, Nam‐Jung; Irle, Stephan; Kay, Steve A.
<x xml:space="preserve">Abstract</x> The front cover picture shows the stabilization of Cryptochrome (CRY) protein by 2‐(9H‐carbazol‐9‐yl)‐N‐(2‐chloro‐6‐cyanophenyl)acetamide (KL044), a new derivative of KL001. CRY is a core component of the mammalian circadian clock, which regulates daily rhythms of physiology and behavior. A ubiquitin ligase complex containing FBXL3 (represented by the hammer) leads to the degradation of CRY through the ubiquitin–proteasome pathway. KL044 binds to CRY and protects it from degradation, resulting in the slowdown of circadian oscillation, about 10 times more potently than KL001. Thus, KL044 is a useful tool to control the circadian clock and also hepatic gluconeogenesis. Cover illustration by Haruko Hirukawa. More details can be found in the Full Paper by T. Hirota, A. Kumar, S. A. Kay et al. on page 1489 in Issue 9, 2015. (DOI: 10.1002/cmdc.201500260).